2020
DOI: 10.1080/10410236.2020.1750764
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Appearance and Homeopathy. Determinants of Trust in Complementary and Alternative Medicine

Abstract: Several studies have investigated the motivations driving the use of complementary and alternative medicines (CAM). Nevertheless, the general public view of these therapies remains relatively unexplored. Our study identifies the social factors that determine a person's trust in alternative therapies, like homeopathy or acupuncture, drawing conclusions from the results of the Spanish National Survey on the Social Perception of Science and Technology (N=6,357).We show that trust in the effectiveness of CAM thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 25 publications
2
23
1
6
Order By: Relevance
“…From these patterns, the CAIM-related content being shared via Twitter would indicate support for CAIM interventions for COVID-19. This is in line with a plethora of published research studies that have found that the general public, across a number of different countries, tend to view CAIMs favourably and their usage continues to increase [61,62,63,64,65]. Over the course of our study, from March to November 2020, though the volume of tweets related to CAIM went down from the peak in May, the sentiments and emotions expressed in tweets were constant.…”
Section: Discussionsupporting
confidence: 90%
“…From these patterns, the CAIM-related content being shared via Twitter would indicate support for CAIM interventions for COVID-19. This is in line with a plethora of published research studies that have found that the general public, across a number of different countries, tend to view CAIMs favourably and their usage continues to increase [61,62,63,64,65]. Over the course of our study, from March to November 2020, though the volume of tweets related to CAIM went down from the peak in May, the sentiments and emotions expressed in tweets were constant.…”
Section: Discussionsupporting
confidence: 90%
“…Although many of the patients who use CAM use it in a strictly complementary manner in addition to conventional treatment, the reality is that alternative use also exists, in which effective treatments are jettisoned for unproven or disproven modalities. Alternative therapy is intimately entangled with yet another darker motivator for CAM acceptance-the perception that there is a conspiracy by pharmaceutical companies and cancer researchers to suppress a cure for cancer (11,12).…”
Section: Science In Societymentioning
confidence: 99%
“…[6,19,20]. Ważne są również takie aspekty, jak dostępność CAM, ich rozpowszechnienie w społeczności oraz tradycje rodzinne korzystania z opieki zdrowotnej wyniesione z domu [21][22][23]. Do najważniejszych zmiennych związanych z silniejszą tendencją do korzystania z CAM należą jednak czynniki poznawcze.…”
Section: Stan Badańunclassified
“…w potrzebie domknięcia [27] przy czym w tej kwestii istnieją rozbieżności w badaniach. Zdecydowanie również rzadziej charakteryzuje ich skłonność do naukowego rozumowania (scientific reasoning) i krytycznego myślenia [28,29] częściej natomiast myślenie magiczne [24,30] oraz wiara w przesądy i teorie spiskowe [24,[31][32][33]. Badania wykazały również, że częściej osoby o pozytywnej postawie wobec CAM wierzą w zjawiska [12,24] oraz inne trudne do wyjaśnienia fenomeny np.…”
Section: Style Poznawcze I Przekonaniaunclassified
See 1 more Smart Citation